2015
DOI: 10.1590/1516-635xspecialissuenutrition-poultryfeedingadditives007-014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Yeast Glucomannan and Sodium Bentonite on the Toxicity of Aflatoxin in Broilers

Abstract: The aim of this study was to evaluate the efficacy of a yeast glucomannan (YG) and sodium bentonite (SB) in reducing the toxicity of aflatoxin for broilers fed a diet naturally contaminated with aflatoxin. In total, 300 7-day-old Ross 308 broilers were randomly assigned to 10 dietary treatments, consisting of a diet with no aflatoxin (positive control), a diet naturally contaminated with 250 ppb aflatoxin (negative control), and eight aflatoxin-contaminated diets supplemented with different SB and YG and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Glucomannans (GM) are extracted from the cell wall of the live yeast Saccharomyces cerevisiae, and were used to prevent the absorption of mycotoxins in the early 1990s (Stanley et al, 1993). It was demonstrated that GM present a strong capacity to bind AF in vivo and in vitro when added to poultry diets (Bintvihok et al, 2002;Karaman et al, 2005;Oguz, 2011;Azizpour & Moghadam, 2015). The positive effect of GM on oxidative stress parameters was also shown in quails (Atalay, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Glucomannans (GM) are extracted from the cell wall of the live yeast Saccharomyces cerevisiae, and were used to prevent the absorption of mycotoxins in the early 1990s (Stanley et al, 1993). It was demonstrated that GM present a strong capacity to bind AF in vivo and in vitro when added to poultry diets (Bintvihok et al, 2002;Karaman et al, 2005;Oguz, 2011;Azizpour & Moghadam, 2015). The positive effect of GM on oxidative stress parameters was also shown in quails (Atalay, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a need for new supplements or synergistic combinations to more efficiently alleviate the deleterious effects of AF and restore liver health and productivity. It has been shown that yeast extracts have the ability to reduce some of the adverse effects of aflatoxicosis in broilers and layers (Zaghini et al, 2005;Matur et al, 2010;Azizpour & Moghadam, 2015). Some plant extracts can also be used in poultry diets to counteract the toxicity of AF (Fouad et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In pigs, the enzymatic activity of gastrointestinal secretions has been improved with the addition of benton-ite (Parisini et al, 1999). In other reports, using bentonite as an adsorbent was effective in minimizing minimizing the toxic effects of aflatoxins on poultry diets and poultry health (Azizpour and Moghadam, 2015). Specifically, when a small amount of bentonite (1%) was added to the diets of laying hens, egg production and egg size increased by 15% and 10%, respectively, and egg shell hardness increased (Nasir et al, 2000).…”
Section: Introductionmentioning
confidence: 99%